Atherosclerosis Impairs Naive CD4 T-Cell Responses via Disruption of Glycolysis. Issue 9 (29th July 2021) - Gaddis, Dalia E.; Padgett, Lindsey E.; Wu, Runpei; Nguyen, Anh; McSkimming, Chantel; Dinh, Huy Q.; Araujo, Daniel J.; Taylor, Angela M.; McNamara, Coleen A.; Hedrick, Catherine C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: CD4 T cells are important regulators of atherosclerotic progression. The metabolic profile of CD4 T cells controls their signaling and function, but how atherosclerosis affects T-cell metabolism is unknown. Here, we sought to determine the impact of atherosclerosis on CD4 T-cell metabolism and the contribution of such metabolic alterations to atheroprogression. Approach and Results: Using PCR arrays, we profiled the expression of metabolism genes in CD4 T cells from atherosclerotic apolipoprotein-E knockout mice fed a Western diet. These cells exhibited dysregulated expression of genes critically involved in glycolysis and fatty acid degradation, compared with those from animals fed a standard laboratory diet. We examined how T-cell metabolism was changed in either Western diet–fed apolipoprotein-E knockout mice or samples from patients with cardiovascular disease by measuring glucose uptake, activation, and proliferation in CD4 T cells. We found that naive CD4 T cells from Western diet–fed apolipoprotein-E knockout mice failed to uptake glucose and displayed impaired proliferation and activation, compared with CD4 T cells from standard laboratory diet–fed animals. Similarly, we observed that naive CD4 T-cell frequencies were reduced in the circulation of human subjects with high cardiovascular disease compared with low cardiovascular disease. Naive T cells from high cardiovascular disease subjects also showed reduced proliferative capacity. Conclusions: These results highlight the dysfunction that occurs in CD4 T-cell metabolism and immune responses during atherosclerosis. Targeting metabolic pathways within naive CD4 T cells could thus yield novel therapeutic approaches for improving CD4 T-cell responses against atheroprogression.